Evaluation of two protocols developed for Xanthomonas albilineas molecular detection in sugarcane - Arriola Benitez, Paula Constanza (2015)
Leaf scald disease caused by Xanthomonas albilineans (Ashby) Dowson is one of the most devastating diseases of sugarcane which has a direct impact on production and manufacturing quality. Currently, molecular tests have been proposed for the detection of this phytopathogen. In this work, two PCR's protocols developed by Pan et al. in 1997 and 1999 were evaluated, with primers that amplify a fragment of the ITS region between the ribosomal genes 16S and 23S. The search of X. albilineans was done from the juice obtained of 35 asymptomatic and symptomatic plants of sugarcane cultivated in localities of the provinces of Misiones and Corrientes, Argentina. X. albilineans was detected in only one of the symptomatic samples but in any of the asymptomatic ones. The protocol developed in 1999 was the one that gave the best results. It is important to emphasize the detection of this phytopathogen in the province of Misiones.